The role of sanitation behavior as a driver for antimicrobial resistance in Escherichia coli among lakeshore residents around Lake Victoria, Uganda - Winston Kabiswa; Joseph M. Kungu; John B. Kalule; Jim Ayorekire; Immaculate Nakalembe; Samuel Majalija (Discover Public Health)
Abstract Background Antimicrobial resistance (AMR) is a growing global public health threat, particularly in low- and middle-income countries like Uganda, where poor sanitation, irrational antibiotic use, and environmental contamination exacerbate its spread. Escherichia coli (E. coli), a common gut bacterium and indicator of fecal contamination, has increasingly been implicated in harboring resistance genes. Communities living along Lake Victoria face heightened risk due to inadequate sanitation, open defecation, improper waste disposal, and informal antibiotic access. Despite these known vulnerabilities, limited research has explored how sanitation behavior influences AMR in lakeshore populations. This study examined the role of sanitation behavior in shaping patterns of AMR in E. coli isolated from stool samples of residents around Lake Victoria. Methods A cross-sectional study design was employed, targeting 120 adults (≥ 18 years) who had resided or worked at the landing sites for at least six months. Stool samples were collected using sterile home collection kits (n = 60 per site) and transported to the National Animal Disease Diagnostics and Epidemiology Centre (NADDEC) for analysis. Isolation and identification of E. coli were performed using standard microbiological and biochemical methods. Antimicrobial susceptibility testing (AST) was conducted using the Kirby–Bauer disk diffusion method against nine commonly used antibiotics, and further confirmed with the VITEK 2.0 COMPACT. Quantitative data on sanitation behaviors and antibiotic use were collected using a pre-tested, semi-structured questionnaire. Data were entered in Excel and analyzed using STATA version 17. Descriptive statistics summarized socio-demographic and behavioral characteristics. Modified Poisson regression was used to assess the association between sanitation behavior and AMR prevalence, with results reported as adjusted prevalence ratios (aPR) at 95% confidence intervals (CIs). Results Out of 120 stool samples collected, 100 (83.3%) were confirmed positive. The overall prevalence of antimicrobial resistance (AMR) among E. coli isolates was 89% (95% CI: 81.1–93.9). High resistance was observed to Tetracycline 58(65.2%) and Ampicillin 58(59.2%), with moderate resistance to Ciprofloxacin 24(25.3%) and low resistance to; Cefepime 5(5.0%), Ceftazidime (6.0%), Amoxicillin-clavulanic acid 7(7.1%), Chloramphenicol 9(9.0%), and Gentamicin 11(11.0%); while all isolates remained susceptible to Meropenem. Behavioral factors significantly associated with increased AMR prevalence included: inadequate toilet sanitation (aPR = 1.14; 95% CI 0.99–1.32; p = 0.058), disposal of child stool into latrines (aPR = 1.24; 95% CI 1.05–1.47; p = 0.011), lack of awareness of the environmental impact of poor waste disposal (aPR = 1.95; 95% CI 0.99–3.85; p = 0.053), generation of chemical waste (aPR = 1.79; p = 0.022), production of trash/debris (aPR = 1.21; 95% CI 1.01–1.44; p = 0.030), and failure to treat water before use (aPR = 1.38; p = 0.006). Conclusion This study highlights the high prevalence of AMR in E. coli among lakeshore residents is strongly linked to poor sanitation behaviors, including inadequate toilet hygiene, improper waste disposal, and untreated water use. Targeted interventions improving sanitation awareness and practices are urgently needed to curb AMR spread in this vulnerable community.